2021
DOI: 10.1158/1535-7163.mct-19-0911
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein-90 Inhibition Alters Activation of Pancreatic Stellate Cells and Enhances the Efficacy of PD-1 Blockade in Pancreatic Cancer

Abstract: ◥Pancreatic ductal adenocarcinoma (PDAC) has a prominent fibrotic stroma, which is a result of interactions between tumor, immune and pancreatic stellate cells (PSC), or cancer-associated fibroblasts (CAF). Targeting inflammatory pathways present within the stroma may improve access of effector immune cells to PDAC and response to immunotherapy. Heat shock protein-90 (Hsp90) is a chaperone protein and a versatile target in pancreatic cancer. Hsp90 regulates a diverse array of cellular processes of relevance to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 52 publications
0
30
0
Order By: Relevance
“…The reason for this is not known and may be related to drug dose [ 115 ]. Growth of TAMs/cancer-associated fibroblasts (CAFs) can be directly inhibited by blocking the PAK1 [ 116 ] pathway or using xl888 (a heat shock protein 90 inhibitor) [ 117 ]. Thus, these two novel therapeutic methods targeting PSCs not only improve T-cell proliferation and infiltration, but also significantly improve the efficacy of ICIs as adjuvants.…”
Section: Research Progress On Treatment With Icismentioning
confidence: 99%
“…The reason for this is not known and may be related to drug dose [ 115 ]. Growth of TAMs/cancer-associated fibroblasts (CAFs) can be directly inhibited by blocking the PAK1 [ 116 ] pathway or using xl888 (a heat shock protein 90 inhibitor) [ 117 ]. Thus, these two novel therapeutic methods targeting PSCs not only improve T-cell proliferation and infiltration, but also significantly improve the efficacy of ICIs as adjuvants.…”
Section: Research Progress On Treatment With Icismentioning
confidence: 99%
“…However, PDAC has a rich fibrotic stroma, and it lack lacks antigen-experienced T effector cells, hence immunotherapy is not effective for pancreatic cancer ( 60 ). The latest research shows that heat shock protein-90 can inhibit PSC/CAF in vitro and enhance the anti-PD-1 blocking effect in vivo ( 61 ). Additionally, in mouse experiments, combining anti-PD-1 and vaccine can have good anti-tumor activity; anti-CD137 agonist antibody combined with anti-PD-1 and vaccine significantly improved the survival time of the mouse PDAC model, highlighting a potential treatment option ( 62 ).…”
Section: Discussionmentioning
confidence: 99%
“…ICG-001, a cAMP-responsive element binding (CREB)-binding protein (CBP)/ β -catenin antagonist, was shown to suppress the activation of PSCs and PSC-induced migration of PCCs ( 169 ). Zhang et al reported that a heat shock protein 90 (Hsp90) inhibitor, XL888, reduced PSC activation, and enhanced the efficacy of anti-programmed cell death protein 1 (PD-1) blockade in tumor-bearing mice ( 170 ). Attempts are also made in reprogramming PSCs by miRNA, a potential therapeutic target ( 206 ).…”
Section: Current Progress In Targeting Strategiesmentioning
confidence: 99%